Avaliação técnico-econômica para remanufatura de estruturas de prensas na fabricação de novos equipamentos - Centoamore, Plinio (2024)
Machine Tools are known as equipment that compose the universe of means of production and are part of fabrication systems spread all over facilities where products for general consumption are fabricated. Within this universe, can be found equipment from different sources and purposes, offering a huge diversity of types and characteristics. This study explored the possibility of implement concepts of sustainability, through circular economy criteria on design and fabrication of new machines tools. This focus search for utilize existing structural elements as a ground zero for the above-mentioned equipment. In terms of this study, it was considered stamping presses used in body shop from automotive industries. This study developed a literature review to locate the selected theme, verifying what is under discussion in relationship of this subject. In order to evaluate the theme development, it was carried out a qualitative research by a survey with specialist participants on the stamping presses market. The survey was performed through interviews, accessing groups of personals that belongs for product engineering department, from commercial areas and from fabrication shop floor. After this, was pursued a development of an algebraic structures, by means of algorithms, which allow a comparative analysis of production costs and fabrication delivery time. To finalize, it was performed a case study to evaluate the algorithm capacities in provide results which can help the decision making action in terms of implement or not to implement the suggested possibility of reuse existing structural elements in design of new machine tools. The results was positive, showed by the qualitative research, using the survey with the specialists. The result is valid since the parts to be reused have been submitted to a quality control inspection to verify their conformity, assuring that they can be installed in new equipment. Using the algorithms on the case study, those presented results that allow the decision makers to assume the possibility of reuse the suggested structural elements. This input certainly can provide confidence on taking a decision, decreasing the risk on this situation.